Emerging technologies and applications for cloud-based gaming - Krishna, P. Venkata (A volume in the Advances in multimedia and interactive technologies (AMIT) book series, 2017)
This book explores the opportunities for the gaming industry through the integration of cloud computing by focusing on design methodologies, fundamental architectures, and the end-user experience.